Pengembangan Alat Peraga Pembelajaran Biologi Berbasis Limbah pada Materi Sistem Peredaran Darah Manusia di SMA N 1 Sipirok - Misla Husnah Pohan; Fery Kurniawan; Almira Amir (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The background of this study is the lack of innovative and environmentally friendly learning media in the biology learning process, especially in explaining abstract concepts such as the human circulatory system. The development of this teaching aid utilizes inorganic waste such as plastic bottles, wood or plywood, cardboard, and used hoses that are easily found in the surrounding environment, thus supporting the principles of environment-based learning and student creativity. This study aims to develop waste-based biology learning aids used in the material on the human circulatory system at SMA Negeri 1 Sipirok. Research and development or known as Research and Development (R&D). The development model used is the ADDIE model (Analysis, design, development, implementation and evaluation). which is modified into several stages, namely: potential and problems, data collection, product design, design validation, design revision, product trial, and final revision. Validity tests are carried out by material experts and media experts, while feasibility tests are carried out through observation and questionnaires of teachers and grade XI students at SMA Negeri 1 Sipirok. The results of the study indicate that this waste-based teaching aid is very suitable for use as a learning medium with a feasibility percentage by material experts of 80% and by media experts of 90%. In addition, the responses of students and teachers to the use of this teaching aid are very positive with an average score above 90.62%. This tool not only helps students understand the concept of blood circulation visually and practically, but also instills awareness of the importance of waste management and creativity in creating useful learning media. Thus, the development of this waste-based biology learning aid can be an innovative and educational solution in improving the quality of biology learning in secondary schools